Implementasi Pemberian Tunjangan Penambahan Penghasilan dan Perbaikan Kinerja Pegawai Dinas Komunikasi dan Informatika di Kabupaten Lamandau - Mamud, Charles Rakam; Christa, Usup Riassy; Isfarudi, Isfarudi (Center of Language and Cultural Studies, 2021)
The purpose of this study was to describe the implementation of providing additional income allowances and improving the performance of employees of the Communication and Information Office in Lamandau Regency. The method used is qualitative. The data were obtained using participatory observation methods, in-depth interviews, and documentation. Research informants are employees of the Department of Communication and Information in Lamandau Regency. To increase the validity of the data, check, recheck, and crosscheck methods were used, as well as prolonging the research time. The data obtained were analyzed using four stages, namely data collection, data classification, data filtering, and drawing conclusions. Based on the results of the analysis, it can be concluded that the provision of additional income allowances for employees of the Lamandau District Communication and Information Office is based on a valid law, namely Regent Regulation number 30 of 2019 concerning the provision of additional income allowances to civil servants within the Lamandau Regency Government. This matter has been communicated to all SKPD and received by all PNS Diskominfo Kab. Lamandau so that the factors that influence policy on resources are sufficient, on target and well implemented.